Analysis of cesarean deliveries in a tertiary hospital as per Robson ten group classification system - Bhardwaj, Bikram; Mansingh, Sudhir; Rai, Gunjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cesarean section is the most commonly performed surgery in the department of gynecology. However, it has its own merits and demerits which affect the mother and the baby in the present as well as subsequent pregnancies. There is a rising trend of cesarean deliveries not only in India but worldwide. So, there is a dire need to audit these cesarean sections and make necessary recommendations accordingly to curb the rising incidence of cesarean deliveries in near future. Hence, the present study analysed the leading groups contributing to high cesarean rates at a tertiary hospital of Armed Forces using Robson ten group classification. Methods: This study was conducted in a Tertiary Hospital of Armed Forces at Chandigarh. All patients who delivered in this hospital between January 2016 to December 2018 were included in this study as per the Robson ten group classification. Results: number of patients who delivered during the time period January 2016 to December 2018 was 3136. Number of patients who delivered vaginally during the same period was 1865. Number of patients who delivered through cesarean section were 1271. Group 5 was the leading contributor to cesarean deliveries followed by groups 2 and 4 subsequently. However, there was significant contribution by group10 to the list. Conclusions: Groups 5, 2 and 4 are the leading contributors to cesarean sections at our institute. So, author need to introspect the labour room protocols and change our norms especially about fetal distress based on CTG monitoring and perform versions in mal-presentations if not contra-indicated to reduce cesarean section rates in near future. Even rising rates of cesarean section in elderly primis, patients conceived after infertility treatment and increasing trends of cesarean delivery on maternal request needs to be checked to reduce the rates of primary cesarean sections.